MANAJEMEN PENINGKATAN EKONOMI MASYARAKAT MELALUI BUDIDAYA KERANG HIJAU DALAM PRESPEKTIF MAQOSID SYARIAH - Muhammad Syauqillah (STAI Ma'had Aly Al-Hikam Malang, 2021)
The economic management of the majority Campurejo village society relies on shellfish aquaculture. They implement shellfish rearing business practice by installing bamboo into the sea in order to catch the shell easier. Shellfish aquaculture is considered as a very promising occupation because it is highly profitable. Campurejo people formerly are categorized as a lower-middle economic society.Phenomenological approach is used as the research method in this study. Moreover, this research uses empirical data with primary data taken from in-depth interviews with several parties which are involved in green shellfish aquaculture activities and the secondary data obtained from many references related to maqashid syariah and others. The data collection techniques using interviews, observation and documentation. In the data analysis aspect, it is through the stages of data reduction, data presentation, verification and conclusion. The author then uses a data triangulation method in order to test the validity of the data.The results shows good economic management in green shellfish aquaculture will lead to profit which has increased the community's economy and at the same time has a chain effect on the economy in terms of education, health, religiosity and child upbringing. The benefits of shellfish aquaculture aside from providing special impacts, also provide general impacts by opening up jobs and helping the underprivileged people. The variety benefits of green shellfish aquaculture has relevance to the spirit of the sharia which intends to prosper the community. Looking at the aquaculture process and the results associated with the implementation of maqasid syariah through the media of maslahah mursalah, it has been in accordance with the implementation requirements. Along these lines, green shellfish aquaculture is a business practice that is actually accommodated in the unwritten scope of sharia.